Envisioning the Future of Fine Dining: Insights from a Multi-Methods Study in Germany - Yana Subbotina-Dubinski; Claus-Christian Carbon (Foods, 2025)
This article investigates predicted future developments in fine dining using a mixed-methods approach rooted in German gastronomic culture. By conducting an inductive media content analysis and ten semi-structured expert interviews with leading figures in Germany’s high-end food sector, we applied a qualitative mixed-methods approach. The study was based exclusively on data collected in 2018 and 2019, deliberately excluding pandemic-related developments in order to focus on long-term structural and cultural trends in fine dining. We identified two core thematic clusters: one related to sustainable food practices (ecology/sustainability, regionality, seasonality, from-farm-to-table, and vegetarianism/veganism) and the other to experiential dimensions of dining (experience, topic-based concept, and storytelling). Our findings contribute to the academic discussion on culinary futures and provide grounded insights into how fine dining is likely to evolve in response to broader societal, environmental, and cultural shifts. This study fills a significant research gap by systematically mapping emerging restaurant concepts based on non-COVID data, making it a valuable reference for scholars and practitioners alike.